Factores laborales y nivel de estrés de las enfermeras del servicio de hemodálisis, de un Hospital de Trujillo - Vitón Vásquez, Nancy Giovany (2016)
This study correlational descriptive, performed with nurses service Hemodialysis Hospital Victor Lazarte Echegaray, in order to determine the relationship between some Labor Factors nurses: time work experience, pay and working conditions with the stress level. The sample consisted of 39 nurses hemodialysis service of Victor Lazarte Echegaray Hospital that made up the sample universe. The results are reported in percentage frequency graphs and statistical analysis criteria "Chi - square" was used which measures the relationship between two variables. Analysis of the results it is concluded: that the employment situation of nurses of hemodialysis service, reveals that the highest percentage of them (76.9%) are employed (48.7%) have a monthly income of 1000-1500 monthly soles, (41%) reported having more than 15 years of professional practice, and (64.1%) have a medium level of stress. Likewise, the analysis of the data confirmed the hypothesis, labor factors: time work experience, pay and working conditions are significantly related to the level of stress as proof of "Chi - square" (X2 = 14.3 p = 0.000; X2 = 4.43 p = 0.035; X2 = 11.5 p = 0.003) respectively statistical significance.